Moral Development in Organizations: A Comparative Study Between Brazil and Portugal - Thiry-Cherques, Hermano Roberto; da Costa Pimenta, Roberto; Tavares Rodrigues, Elaine Maria (Revista ADM.MADE, 2012)
<!--[if gte mso 9]> Normal 0 false false false PT-BR JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> In this article, we examine the main ethical conditioners regarding the perception of moral development at the managerial level of organizations. It aims to present a classification of the level of moral development on Brazilian and Portuguese organizations, as a matrix of relationships that compares declared mobiles and modalities of actions. Based on the data obtained in Brazilian and Portuguese organizations and the interpretative analysis conducted, this research revealed differences that indicate a level of development between pre-conventional and conventional for organizations in Brazil and a level of moral development between conventional and post-conventional for organizations in Portugal. <!--EndFragment-->